Assessment on factors affecting human wild animal coexistence and associated mitigation measures in the buffer zone community of Shivapuri Nagarjun national park, Nepal - Dipesh Raj Pant; Kuaanan Techato; Siriporn Pradit; Saroj Gyawali; Binod Baniya (Environmental and Sustainability Indicators)
Solid success in conserving the protected areas would obviously require the participation and cooperation from local people particularly in developing countries where the locals bear most of the expense of Human wildlife co-existence. Considering this, the present research attempts to explore the factor affecting Human-Wildlife Co-existence (HWC) and the related mitigation measures adopted by the buffer zone community of Shivapuri Nagarjun National Park, Nepal (SNNP). The research also intends to determine the livelihood status of the locals, policies and compensations offered by buffer zone management. Data for the quantitative approach has been collected from 446 households residing in the buffer zone regions through structured questionnaire. Qualitative data are fetched through nine KII (Key Informant Interviews) who were the stakeholders of the buffer zone community. The overall results of the research find that locals in the buffer zone of SNNP are affected by the wildlife interventions. Due to this, crop damage is regarded as the massive loss experienced, wild boar is found to be the major conflicting wildlife followed by monkey and leopard. Local people are observed to have positive attitude towards the policies and programs of buffer zone management particularly, fuel-wood supply is the most appreciated benefits proffered.